Keys to Latin America and the Caribbean - Mayobre, Eduardo (SELA CaracasVE, 1996)
Sketches the main characteristics of the region's economic evolution explaining its recent performance on the basis of fiscal, monetary, trade and financial policy. Analyzes the current situation and the prospects vis-a-vis two crucial factors, namely regional integration and foreign investment.